#NeverAgainMSD Student Activism: Lessons for Agonist Political Education in an Age of Democratic Crisis. Issue 6 (21st June 2021) - Abowitz, Kathleen Knight; Mamlok, Dan
Abstract : In this essay, Kathleen Knight Abowitz and Dan Mamlok consider the arguments for agonist political education in light of a case study based in the events of the 2018 mass shooting at Stoneman Douglas High School in Parkland, Florida, and the subsequent activism of its survivors. We use this case to examine agonist expressions of citizenship, and to present an argument for framing agonist politics through the lens of Deweyan transactional communication combined with the critical concept of articulation. A major lesson in this case is the significance of citizenship learning that prioritizes challenging the political status quo along with working to reestablish new political relations on grounds that are more just. The authors argue that the endgame of agonist‐informed political education should be that which helps students, as present and future citizens, reconstruct existing political conditions. Knight Abowitz and Mamlok conclude with suggestions for four domains of knowledge and capacities that can productively shape agonist citizenship education efforts: political education, lived citizenship, critical political literacies, and critical digital literacies.